Cutaneous Squamous Cell Cancer on the Waistline Associated with Saree-wearing: A Case Report and Literature Review - Jeva Cernova; Muhammad Hyder Junejo; Marcin Ligaj; Fawad Hussain; Catherine A. Harwood (Acta Dermato-Venereologica, 2023)
Abstract is missing Short communication